ASSESSMENT OF INDIVIDUAL RESEARCH PERFORMANCE FOR UK AND IRISH ACCOUNTING AND FINANCE ACADEMICS - Tower, Greg; Rusmin; Brown, Alistair; Lee, Alina; Goforth, Emily; Porter, Stacey; Scully, Glennda; Singh, Inderpal; Taylor, Grantley; Ke, Kenneth; Tian, Kevin; Neilson, John (The journal of contemporary issues in business and government, 2008)
As a way of evaluating the successful implementation of a national research assessment, this study measures the individual research performance of 1,572 UK and Irish accounting and finance academics in the period 2004-05, twenty years after the implementation of the increased research focus in the UK through the Research Assessment Exercise (RAE). The findings show surprisingly low levels of research productivity with the average accounting and finance academic publishing less than one half of one publication per annum. Using two measures of quality—Journal Impact Factors and the existence of Social Science Citation Index articles— the results reveal an even sparser picture with only 11 percent of these academics publishing their research in the most prestigious journals over a two year period. Doctoral-trained male professor or associate professor level academics from older universities were found to be more likely to produce high quality publications. These demographic data should raise concerns for research policymakers and research academics alike as they demonstrate a disparity in favour of an already well funded, high performing minority. The overall low level of accounting and finance academic productivity in the UK, after 20 years of regular scrutiny, raises major concerns about the efficacy of such all-encompassing national RAEs. Advocacy of a simpler, less intrusive approach such as the Dutch system is advanced.